NEBIVOLOL SAFETY AS CARDIOSELECTIVE Β-BLOCKER IN COMPLEX THERAPY IN PATIENTS WITH ISCHEMIC HEART DISEASE ACCOMPANIED BY CHRONIC OBSTRUCTIVE BRONCHITIS - Zh. G. Simonova; E. I. Nfhkjdcrfz; A. K. Tarlovskiy (Российский кардиологический журнал)
The influence of cardioselective β1-blocker Nebivolol on external respiration function in patients with ischemic heart disease accompanied by chronic obstructive bronchitis was studied. 39 patients randomized on 2 groups were examined. The basic group (n = 20) took nebivolol in daily dose 5 mg, the control group (n = 19) took placebo. The duration of therapy was 30 days. External respiration function was investigated by spirographic method on "Spirograph SP 01 "K" before and after the treatment. The following indicator were observed: lung vital capacity (LVC), forced LVC (FLVC), forced expiratory volume (FEV1), Tiffno index (FEV1 / FLVC), maximal free pulmonary breathing capacity (FPBC), peak expiratory flow rate (PEFR) 25 % LVC (PFR 25 % - patency of large bronchus), PFR 50 % (patency of mean bronchus) PFR 75 % (patency of small bronchus). Initially all patients had trachea-bronchial permeability abnormalities. There was evident antianginal action in time of nebivolol therapy. Impairment of external respiration function rates was not been observed.